Efficacy of cognitive behavioral therapy with paroxetine and paroxetine only for social anxiety disorder: A behavioral, placebo-controlled study - Samantray, Narendranath (Ind Psychiatry J, 2019)
BACKGROUND: Individually, cognitive behavior therapy (CBT) and paroxetine (PX) are considered as frontline treatments for social anxiety disorder (SAD). However, the possibility of combined interventions of these might be more helpful than either intervention alone has met with mixed reviews. Hence, the goal of the current study was to examine whether combining CBT + PX would be superior to PX alone in the treatment of SAD in various stages of treatment. METHODOLOGY: The present study is a single-center, rater-blind, behavioral placebo (Bh. PBO)-controlled study. Sixty-seven participants were prospectively observed in two groups, one receiving CBT + PX and PX + Bh. PBO for 24 weeks. The Social Interaction Anxiety Scale (SIAS) was measured at pre, post (12 weeks), end of booster (24 weeks), and 2-month follow-up (32 weeks) stage. The SIAS was measured at pre, post (12 weeks), end of booster (24 weeks), and 2-month follow-up (32 weeks) stage. RESULTS: Both treatment groups have significant difference in the mean scores of SIAS in posttreatment, booster, and follow-up stages from their respective mean scores at prestage. Mann–Whitney U-test found no significant differences in the mean scores of SIAS between CBT + PX and PX + Bh. PBO at posttreatment and booster phase, whereas a statistically significance difference (P = 0.03) was found in 2-month follow-up stages. Both treatment groups have large effect size in posttreatment and end of booster phase. At 2-month follow-up stage, a large effect size of 1.11 was found in CBT + PX group as compared to medium size of 0.6 in PX + Bh. PBO group. CONCLUSIONS: Combined treatment of CBT + PX provided no advantage over PX + Bh. PBO in acute stages of treatment, but the former have significantly better maintenance of treatment gains in 2-month follow-ups than the latter.